Mothering Sons: Stories by Findley, Hodgins and MacLeod Uncover the Mother's Double Voice - Kruk, Laurie (Atlantis)

(untitled) (Mount Saint Vincent University, 2007)
Maternal feminist criticism argues that we are culturally constructed, but also recognizes the embodied experiences of mothers. This maternal "double voice" shifts between subject/object, passive/active and resistant/conforming positions. "Mothering sons" reciprocate the maternal practice of preservation by supporting this "double voice."